Power transfer capability enhancement with optimal maximum number of facts controllers using evolutionary programming - Chansareewittaya S. (2014)
In this paper, evolutionary programming (EP) with optimal maximum number of FACTS controller and search space managing methods are proposed to determine the optimal allocation of FACTS controllers to enhance power transfer capability of power transactions between generators and load buses. Particular optimal allocation includes optimal locations and parameter settings. Two types of FACTS controllers including thyristor-controlled series capacitor (TCSC) and static var compensator (SVC) are used individually in this study. The objective function is formulated as maximizing total transfer capability (TTC) and minimizing power losses. Power transfer capability determinations are calculated based on the optimal power flow (OPF) technique. Split and non-split search space managing methods are used. Test results on IEEE 118-bus system and the practical Electricity Generating Authority of Thailand (EGAT) 58-bus system showed that EP with optimal maximum number of FACTS and the proposed split search space managing method gave higher TTC and less maximum number of FACTS controllers than those from non-split method. Therefore, the installation of FACTS controllers with optimal maximum number and optimal allocation are beneficial for the further expansion plans. © 2011 IEEE.